Toward cleaner production: What drives farmers to adopt eco-friendly agricultural production?. (20th May 2018) - Zhang, Liguo; Li, Xuerong; Yu, Jiangli; Yao, Xiaoli
Abstract: Due to the indiscriminate use of chemical inputs like pesticides, serious agricultural diffused pollution is arising, not only with the ecological environment damaging, but also with the agriculture sustainable development restricted. It is imperative for China to reduce pesticides use. Under the decentralized production background, farmers' willingness to reduce pesticides is worth discussing. This paper aims to explore farmers' willingness to reduce pesticides use based on its determinants analysis. A structured questionnaire was administered to a random sample of 924 farmers in rural China. Binary logistic regression model was used to examine the determinants. The results showed that farmers' environmental concern, pesticides residues cognition, agro-products quality concern and input controls positively and significantly influence farmers' willingness to reduce pesticides, while non-agricultural income share influence negatively. Results also reveal that farmers' self-discipline is more effective than government regulations; enhancing farmers' self-discipline is important to guide farmers toward environmentally-friend measures in agricultural production. This paper recommended that policy makers take measures to improve farmers' environmental awareness and strengthen input supervision. Improved effectiveness of pesticides usage is also needed. Highlights: Determinants of eco-friendly agricultural production are investigated. Nine constraints which affects farmers' production behavior are identified. Farmers' self-discipline is more effective than government regulations.